Safety and antidepressant efficacy of selective serotonin re-uptake inhibitors - Kasper, S.; Höflich, G.; Scholl, H.-P.; Möller, H.-J. (Human Psychopharmacology: Clinical and Experimental, 1994)
This review deals with the safety and antidepressant efficacy of selective serotonin re-uptake inhibitors (SSRIs). At present, 5 SSRIs are used therapeutically in European countries (fluvoxamine, fluoxetine, paroxetine, sertraline, and citalopram). The antidepressant efficacy of these drugs has been tested both vs placebo and vs reference antidepressants (amitriptyline, imipramine), revealing comparable antidepressant efficacy to the active compounds and a significant superiority compared with placebo. Available studies provide initial evidence that SSRIs have good antidepressant efficacy in severe depression and suggest that they might lead to a faster decline of suicidal tendencies within major depression. Since they have a favorable side-effects profile in sum, compared with tri- and tetracyclic antidepressants, they can be recommended from the aspect of a 'side-effects-derived indication.' (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Drug Therapy; Fluoxetine; Fluvoxamine; Major Depression; Paroxetine; Serotonin; Side Effects (Drug); side effects & antidepressant efficacy of selective serotonin reuptake inhibitors